Selection of Maize Genotypes with Tolerance to Osmotic Stress Associated with Salinity - Collado, Mónica B. (2016)
Thirteen different inbred lines in relation to the type of grain and life cycles were characterized by testing for osmotic stress associated with salinity. The identification of tolerant genotypes would be an effective strategy to overcome the saline stress. Osmotic stress reduces immediately the expansion of the roots and young leaves which determine a reduction in the size of the plant. A completely randomized design was adopted to test seedlings under controlled conditions of light and temperature. Two treatments were used: 0 mM NaCl (as control) and 100 mM NaCl. After 15 days of complete salinization, the seedlings were harvested and several morphological traits were measured. The morphological traits of growth were leaf growth (Ar1, Ar2, Ar3 and Ar4), dry masses of shoot and root (SDM and RDM, respectively). Also, traits associated with water economy were registered: leaf water loss (LWL) and relative water content (RWC). The morphological traits were expressed in relative terms, while the traits associated with the economy of water were expressed in absolute terms. Uni and multivariate techniques were applied to identify genotypes with divergent behaviors to osmotic stress tolerance. Also, a Tolerance Index was employed to identify superior genotypes. Four clusters were obtained after applying a Cluster Analysis and Principal Component Analysis (PCA). The genotypes were compared to each other with a test of DMS. The results obtained with different statistical techniques converged. Some variables presented a differential weight classification of genotypes. The morphological traits like RDM, SDM, Ar3, Ar4 and Ar5 were the most discriminating. Tolerance Index allowed to classify genotypes, thus SC2 and AD3 lines were that reached highest value of the index and therefore would be tolerant lines, while AF3 and LP3 had a low index and were seen as sensible.